Carpological Studies-an Aid to the Identification of Indian Trees: Terminalia Linn - Biswas, S.A.S.; Kukreti, Sharad (Indian Forester, 1992)
For the systematic studies on the forest flora of any region it is often required to identify a fruit or seed without recourse to any other plant material. In absence of any consolidated account or manual on seed or fruit taxonomy of Indian species the correct identification of species becomes a tedious task. The present investigation is aimed at identification of 20 species of Terminalia with the aid of carpological studies. The species have mainly been categorised into five groups, viz. I-wingless (9 spp). II-flatly-winged (I sp). III-2 winged (3 sp.), IV-Â± 3 winged (I sp.) and V-5-winged (6 spp.). Studies reveal that N.E. India, South India and Andaman & Nicobar Is. Regions are extremely rich in species diversity and represent wingless to 5-winged categories of fruits. Illustrations of carpological materials and a table showing distribution of species in different parts of India and adjoining countries are given. The species have been provided with carpological description, important vernacular names and phenology.